Pharmacy Student Knowledge, Confidence and Attitudes Toward Medical Cannabis and Curricular Coverage - Caligiuri, Frank J. (Am J Pharm Educ, 2018)
Objective. To assess pharmacy student confidence in their knowledge of qualifying conditions for medical cannabis use in the US and their attitudes toward curricular coverage of medical cannabis. Methods. Students were asked to complete an electronic survey to measure knowledge and confidence in various domains of medical cannabis treatment, including qualifying conditions, adverse effects, and other patient care skills. Results. There were 238 students who completed the survey. Responses to all domains and their corresponding confidence levels displayed a lack in confidence. The only domain wherein students had confidence in was their ability to retrieve related drug information. Nearly 80% of students felt that the topic of medical cannabis should be added to existing curricula within the next five years. Conclusion. With the prevalence of cannabis programs and knowledge gap, pharmacy schools should consider coverage of medical cannabis in the curricula.